Unity of opposites: a structured way to promote geographic understanding - Canfei He; Hantian Sheng (Annals of GIS)
Unity of opposites, as a key manifestation of the theory of contradiction, has embedded in ancient naive world view of the spatial dialectics raised by philosophers as well as Marxist geographers. Geography, as a discipline with a long history, emphasizes the implementation of description and illustration. However, as the phenomena to be explained become more complex, sophisticated methodologies such as spatial analysis and statistical models have been extensively used to explore the deeper mechanisms. Such a progress shows that geographic understanding has gradually moved from the empirical domain to the real domain, in which critical realism has been regarded as a pivotal way to reveal the ontology of geography. Within the scope of critical realism, in this paper, we propose that unity of opposites provides a structured way to distinguish geographical mechanisms as well as to underpin the design of empirical studies. We use two empirical cases to show that unity of opposites as a structured way of thinking corrects the biased spatial description, contributing to the formation of an inclusive and conclusive empirical framework. Last but not least, we call for further integration of the idea of unity of opposites in the future geographic research. In doing so, the current ambiguities in pluralistic mechanisms can be better addressed.